Дослідження регенеративних вібрацій при різанні - Кондратюк, Олег Леонідович; Скоркін, Антон Олегович; Литвинова, Олена Олегівна (Eastern-European Journal of Enterprise Technologies, 2010)
The impact of recovery vibrations during cutting are considered, the experimental researching, in which the impact of cutting speed, depth and face angle was determined, are given